Detection of Rickettsia spp. and Bartonella spp. in Ctenocephalides felis fleas from free‐ranging crab‐eating foxes (Cerdocyon thous). Issue 4 (8th March 2019) - Schott, D.; Souza, U. A.; Dall'Agnol, B.; Webster, A.; Doyle, R.; Peters, F.; Favarini, M.; Mazim, F.; Rosa, A. O.; Jardim, M. M. A.; Trigo, T. C.; Reck, J.
Abstract: Fleas are insects with a worldwide distribution that have been implicated in the transmission of several pathogens. The present study aimed to investigate the presence of Rickettsia spp. (Rickettsiales: Rickettsiaceae) and Bartonella spp. (Rhizobiales: Bartonellaceae) in fleas from free‐ranging crab‐eating foxes Cerdocyon thous (Linnaeus, 1766) (Carnivora: Canidae) from Rio Grande do Sul, southern Brazil. Fleas were collected manually from animals and used for the molecular detection of Rickettsia spp. and Bartonella spp. Twenty‐nine C. thous were sampled in six municipalities. Four foxes were parasitized by 10 fleas, all of which were identified as Ctenocephalides felis (Bouché, 1935) (Siphonaptera: Pulicidae). DNA from Rickettsia felis Bouyer et al ., 2001 and Rickettsia asembonensis Maina et al ., 2016 were found in three and eight fleas, respectively. In four fleas, DNA of Bartonella sp. was identified. Phylogenetic analysis grouped Bartonella sp. together with other genotypes previously reported in C. felis worldwide. The scenario described in the present study highlights a Neotropical canid parasitized by the invasive cosmopolitan cat flea, which in turn, is carrying potentially invasive vector‐borne microorganisms. These findings suggest that C. felis is adapted to wild hosts in wilderness areas in southern Brazil, hypothetically exposing the Neotropical fauna to unknown ecological and health disturbances. Abstract : In the present study, the flea species of 29 free‐ranging Cerdocyon thous (Carnivora: Canidae) live‐trapped in Southern Brazil were investigated. Four C. thous were parasitized by 10 fleas, all of which comprised Ctenocephalides felis (Siphonaptera: Pulicidae), the common cat flea. The DNA of Rickettsia felis, Rickettsia asembonensis and Bartonella sp. were detected in fleas using molecular methods.